Features of motivation for success and willingness to take risks among students of the faculty of physical education and sports of the pedagogical university with an androgynous gender type - Shustova L.P.; Danilov S.V.; Ilkin A.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study the characteristics of motivation for success and willingness to take risks among students of the Faculty of Physical Education and Sports of a pedagogical university with an androgynous gender type. Methods and structure of the study. The scientific work was carried out at the Ulyanovsk State Pedagogical University on a sample of full-time undergraduate students of the 1st-4th year of the Faculty of Physical Culture and Sports. Analysis of the results of modern research, synthesis, and generalizations were used as theoretical research methods. The empirical method was a ascertaining experiment, using the personality diagnostic method for motivation for success by T. Ehlers, the diagnostic method of the degree of risk readiness by G. Schubert and the questionnaire by S. Boehm. Results and conclusions. Analysis of primary sources revealed a direction of research related to the study of student-athletes’ motives for sports achievements and professional development. However, these studies do not fully describe the relationship between the motivational characteristics of sports department students and their gender characteristics. During the implementation of the experimental part of the study, it was found that in a sample of students heterogeneous in gender composition, the androgynous type of gender is predominant. Such students are motivated to achieve success; most of them are characterized by a high level of motivation. The willingness to take risks in androgynous students is manifested to a lesser extent than the tendency to be cautious. At the same time, no significant connection was found between motivation to achieve success, on the one hand, and the tendency to behave cautiously, or willingness to take risks, on the other. There was also no obvious connection between the level of motivation to achieve success and the propensity to take risks with team or individual sports of students. The results obtained during the study can be used in the development of sports tasks and exercises that combine a focus on success with an optimal amount of risk in both individual and team sports.